Environmental Exposures, Clinical Allergy Symptoms, and Serum IgE in Young Adults: A Cross-Sectional Study from Makassar, Indonesia - Andi Khairul Anaam; Liong Boy Kurniawan; Sitti Rafiah; Andi Alfian Zainuddin; Uleng Bahrun (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The global prevalence of allergic diseases has increased significantly, particularly among young adults. Immunoglobulin E (IgE) plays a central role in the pathophysiology of allergic responses and is considered a crucial biomarker in evaluating allergic sensitivity. However, the influence of environmental exposures and clinical complaints on serum IgE levels in adult populations remains understudied, especially in tropical developing countries. Methods: This study aimed to analyze the relationship between environmental factors and clinical complaints with serum IgE levels in a population of healthy young adults in Makassar, Indonesia. A cross-sectional study was conducted involving 80 healthy adults aged 18–40 years. Environmental exposures and clinical symptoms were analyzed against serum IgE levels. Non-parametric tests (Mann-Whitney U and Kruskal-Wallis) showed no significant associations. However, in the multivariate regression model, humidity was the only environmental factor significantly associated with serum IgE concentration. Results: The mean serum IgE level among participants was 176.8 IU/mL (SD ±196.9), with a wide distribution. No statistically significant associations were found between serum IgE levels and clinical complaints such as asthma, allergic rhinitis, and atopic dermatitis (p > 0.05). Similarly, environmental exposures including cigarette smoke, dust, pet dander, and poor ventilation were not significantly related to IgE levels. Notably, high environmental humidity was negatively associated with serum IgE levels (p = 0.047). Most environmental factors and clinical complaints assessed in this study were not significantly associated with serum IgE concentrations in healthy young adults. Conclusion: The observed inverse association with high humidity suggests a potential modulatory role that warrants further investigation. Future longitudinal studies with larger samples are recommended to confirm these findings and provide stronger evidence to inform public health strategies in allergy prevention.